Education and Entrepreneurship: Policy Review of South Asian Countries - Rai, Krishna Bahadur (International Journal of Social Sciences and Management, 2018)
In south Asian countries, the education policy makers and educators have been highly focusing to the development of entrepreneurship through the educational interventions. The courses of entrepreneurship development have been endorsed to the schools and universities. But, the domestic enterprises have been declining gradually. The paper aims to present the issues on modern education system and its role in mainstreaming of domestic enterprises in these countries. For looking the connections between these two phenomena, I collected and reviewed the existing policies and practices regarding education system and entrepreneurship development. The study explored that the modern education system have not been supporting to the domestic enterprises in south Asia and the citizens are on the 'middle of the road' of their entrepreneurial practices. The recommendation is that the educational policies and practices should be reviewed and implemented effectively to promote the domestic enterprises; otherwise, those enterprising activities will be declined for forever. The findings of this study have the implications to ensure the educational policies for promoting these enterprises. Int. J. Soc. Sc. Manage. Vol. 5, Issue-2: 60-68